Serum Protein D Surfactant Level Based on Length of Exposure in Workers at the Supit Urang Waste Disposal Site, Malang - Zata Dini; Tri Wahju Astuti; Rezki Tantular (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Waste collectors are at risk of developing lung disease due to exposure to bioaerosols from organic and inorganic materials. The function of surfactant protein D (SP-D) is as innate immunity that protects the lungs.  Exposure to bioaerosols in landfills causes inflammatory reactions which can increase the permeability of the blood-lung barrier. As a result, SP-D will leak into the plasma. AIMS: This study aims to analyze serum SP-D levels in relation to length of exposure in waste collectors. METHOD: This analytical, cross-sectional study was done in a Supit Urang waste disposal site, Malang, Indonesia. Samples for serum SP-D analysis were taken from peripheral blood samples and analyzed with ELISA technique. RESULT: There were 68 subjects, consisting of 24 subjects with exposure duration of 5 years, 14 subjects of 5-10 years, and 30 subjects with exposure of 10 years. The number of smokers and non-smokers were 36 and 32 subjects respectively. Significant differences in SP-D serum levels were found between different exposure durations, particularly with exposure of more than 5years. A significant positive correlation was obtained between serum SP-D levels and exposure duration (r = 0,585; p = 0,000). Meanwhile, there was no significant difference in serum Sp-D levels based on smoking status (p=0.112). CONCLUSION: Length of exposure significantly affected SP-D serum levels in waste workers, especially with exposure of more than 5 years.